2015
DOI: 10.1039/c5dt03188e
|View full text |Cite
|
Sign up to set email alerts
|

New honeycomb iridium(v) oxides: NaIrO3 and Sr3CaIr2O9

Abstract: We report the structures and physical properties of two new iridates, NaIrO 3 and Sr 3 CaIr 2 O 9 , both of which contain continuous two-dimensional honeycomb connectivity. NaIrO 3 is produced by room temperature oxidative deintercalation of sodium from Na 2 IrO 3 , and contains edge-sharing IrO 6 octahedra that form a planar honeycomb lattice. Sr 3 CaIr 2 O 9 , produced via conventional solid-state synthesis, hosts a buckled honeycomb lattice with novel corner-sharing connectivity between IrO 6 octahedra. Bot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 37 publications
3
34
0
Order By: Relevance
“…The Sr 3 CaIr 2 O 9 phase, on the other hand, remains non-magnetic due to its J ef f = 0 ground state, consistent with a recent powder study. 51 The heavily substituted single crystals in the Ca 5 Ir 3 O 12 phase show an AF phase transition at T N = 9K; however at higher temperatures an anomalous anisotropy is observed in the local moment behavior. Our data provide a global view of the evolution of the ambient pressure electronic ground states and lattice stabilities of Sr-214 as increasing chemical pressure is introduced via isovalent substitution of smaller Ca cations.…”
Section: 32mentioning
confidence: 99%
See 1 more Smart Citation
“…The Sr 3 CaIr 2 O 9 phase, on the other hand, remains non-magnetic due to its J ef f = 0 ground state, consistent with a recent powder study. 51 The heavily substituted single crystals in the Ca 5 Ir 3 O 12 phase show an AF phase transition at T N = 9K; however at higher temperatures an anomalous anisotropy is observed in the local moment behavior. Our data provide a global view of the evolution of the ambient pressure electronic ground states and lattice stabilities of Sr-214 as increasing chemical pressure is introduced via isovalent substitution of smaller Ca cations.…”
Section: 32mentioning
confidence: 99%
“…51 No relaxation of the structure into a higher symmetry space group was observed as the system was heated to 473 K; however our PXRD measurements have poor sensitivity to the oxygen site positions and occupancies. Minimal anisotropy was observed in both transport and magnetization measurements, and our magnetization data are consistent with the picture of Sr 3 CaIr 2 O 9 possessing a non-magnetic J = 0 ground state.…”
mentioning
confidence: 99%
“…Recently the real structures of related stacking faulted iridates with honeycomb like lattices were successfully described by super positioning of different stacking types. 10,11 Based on these approaches possible stacking orders of the layers are derived from structural considerations.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…O'Malley et al 9 observed the occurrence of stacking faults in the crystal structure of α-Li 2 IrO 3 , which is a common phenomenon in layered alkali-and earth alkali metal iridates. 10,11 Hence the slight occupational disorder between Li + and Ir 4+ in the layers, which was introduced to the structural model during the refinement, could be an artefact from daubed reflection intensities due to diffraction line broadening by the appearance of stacking faults. 10,11 The overall structural motif of α-Li 2 IrO 3 is closely related, but not identical to LiCoO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation